(untitled) (Res Medica, 2014)
A dissertation read before the Society on Friday, 24th February, 1967. The concept of what constitutes cruelty to children is best described in the Children and Young Persons Act as “Assault, ill-treatment, neglect, abandonment or exposure such as will cause unnecessary suffering or injury to health, including any mental derangement.”